Radiation Exposure during Elective Endovascular Abdominal Aortic Aneurysm Repair: A Nationwide Study of Patient Doses in Finland - Laurén, Jouni; Kaasalainen, Touko; Kesävuori, Risto; Nikulainen, Veikko; Suominen, Velipekka; Hakulinen, Ullamari; Karjalainen, Jari; Kariniemi, Juho; Venermo, Maarit; Aho, Pekka; Finnish Radiation Safety Collaboration Group (Elsevier, 2026)
Objective
Endovascular aneurysm repair (EVAR) predisposes patients to significant radiation exposure, with well known harmful effects. This study aimed to assess the radiation doses and their consistency in Finland and to investigate the factors affecting the doses, to potentially allow future dose reductions.
Methods
This retrospective, nationwide, multicentre study included all patients who underwent an elective standard EVAR procedure in Finland between 2017 – 2022. Data were collected from: body mass index (BMI); fluoroscopy time (FT); radiation exposure, including kerma area product (KAP) and cumulative air kerma at the patient reference entrance point (Ka,r) from fluoroscopy and digital subtraction angiography (DSA); number of DSA series; and exposure parameters of the angiography systems. Descriptive statistics and linear regression analyses were performed to identify the parameters that significantly influenced radiation exposure.
Results
A total of 1 185 EVAR procedures from all five centres that perform EVAR in Finland were included in the study. Large variation in medians of total procedure KAP between the centres was observed, ranging 22.5 – 135.0 Gy·cm2. Median FT ranged 16.1 – 29.1 minutes. Both fluoroscopy and DSA showed large variation in radiation exposure. BMI did not significantly differ between the centres. The factors significantly affecting the dose in the multivariate linear regression model were BMI, FT, number of DSA acquisitions, DSA frame rate, and maximum copper filtration in fluoroscopy.
Conclusion
Surprisingly high, up to six fold, intercentre variability in total procedure radiation exposure was observed. The variability in the doses was mostly attributable to differences in exposure parameters (e.g., dose at detector level, copper filtration, and pulse rate); the manner in which radiation is utilised also played a significant role. In other words, both angiography system parameters and the working habits of the operator need to be optimised.